Stable potential formation with neutral and dust particles in expanding magnetic field near divertor plate - Tomita, Yu.; Chutov, Yu.I. (Вопросы атомной науки и техники, 2002)
The effects of neutral and dust particles for the stable or monotonically changing potential formation in an expanding magnetic field toward the divertor plate was investigated in a quasi-neutral plasma by using one-dimensional kinetic analysis. Unless there are plasma ion sources, such as ionization of neutral particles, the required ion flow velocity for injected ions to form the stable potential has to be larger than an ion sound velocity, i.e. the generalized Bohm’s criterion. It was clarified that the plasma ion sources mitigate this requirement. On the other hand, since the dust particles decrease the plasma ion density due to absorption to them, the required ion flow velocity for injected ions increases. The numerical values of these effects are presented. The decreasing magnetic field in a plate direction also increases this required velocity.